Intrinsic electronic transport properties of organic field-effect transitors based on single crystalline tetramethyltetraselenafulvalene - Nam, M; Ardavan, A; Cava, R; Chaikin, P (2003)
The electronic transport properties of organic field-effect transistors (OFET), constructed on the highly anisotropic semiconductor, tetramethyltetraselenafulvalene (TMTSF), were discussed. The results show that transport properties are largely dominated by small polaron formation. An intrinsic hopping mechanism was found to govern the electronic transport in TMTSF OFETs. A maximum mobility of 0.2 cm 2/V s at room temperature was reported.